2000
DOI: 10.2106/00004623-200009000-00054
|View full text |Cite
|
Sign up to set email alerts
|

Late-Preconditioning Protection is Evident in the Microcirculation of Denervated Skeletal Muscle

Abstract: Summary:We investigated whether ischemic preconditioning induces microvascular protection in skeletal muscle at the late phase (after 24 hours) when the same muscles are subjected to prolonged warm global ischemia. The cremaster muscle of the male Sprague-Dawley rat underwent vascular isolation and was subjected to 4 hours of ischemia and 60 minutes of reperfusion. Early preconditioning consisted of 45 minutes of ischemia followed by 15 minutes of reperfusion before prolonged ischemiaireperfusion; late precond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Data investigating the effects of ischemic preconditioning on the microcirculation have shown that it prevents microcirculatory vasoconstriction and no-flow events after a later ischemic event (Wang et al, 1996;Wang et al, 1999), but the acute effects of ischemic preconditioning on microvascular density have not been well studied. NIRS monitoring enables quantification of the oxy-and deoxy-hemoglobin contents, in a fixed area of tissue (dependent on the distance between the optodes), and the sum of these values is given as the THI (Mancini et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Data investigating the effects of ischemic preconditioning on the microcirculation have shown that it prevents microcirculatory vasoconstriction and no-flow events after a later ischemic event (Wang et al, 1996;Wang et al, 1999), but the acute effects of ischemic preconditioning on microvascular density have not been well studied. NIRS monitoring enables quantification of the oxy-and deoxy-hemoglobin contents, in a fixed area of tissue (dependent on the distance between the optodes), and the sum of these values is given as the THI (Mancini et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…9À11 Each study used a different IPC protocol: two used the same ischemic challenge, and one reported a controversial result. Pudupakkam et al 10 preconditioned with five 10-min cycles of ischemia/reperfusion and challenged muscles with a 2-h ischemic insult, while Wang et al 11 used a single 45-min cycle of ischemia/reperfusion and challenged muscles with a 4-h ischemic insult. Both studies prevented the no-reflow phenomenon and attenuated vasospasm during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is the late phase that provides protection during the period when most microsurgical problems usually arise. We have reported that microcirculatory alterations do not take place in rat cremaster muscle if 4 h of warm ischemia is preceded by IPC [54][55][56][57][58][59][60]. We have conducted several studies investigating the mechanisms of late preconditioning.…”
Section: Ischemic Preconditioningmentioning
confidence: 99%